Tratamento da síndrome das pernas inquietas idiopática: revisão sistemática e metanálise - Conti, Cristiane Fiquene [UNIFESP] (2009)
Background: The restless legs syndrome (RLS) is a disorder characterized by a distressing need to move the legs and sometimes other parts of the body. Usually accompanied by a marked sense of discomfort or pain in the leg or other body part affected. The treatment of restless legs syndrome with dopamine agonists has been recognized as the main first-line treatment because it seems to be effective based on pathophysiologic principles. Although, several pharmacological drugs are envolved in the treatment of RLS. Objectives: To assess whether pharmacological interventions are effective and safe for the treatment of RLS. Methods: Systematic Cochrane Review of randomized studies or quasi-randomized on pharmacological agents used to treat RLS. The following outcomes were assessed for each drug: relief of symptoms measured by the restless legs syndrome ranting scale (IRLSSG Rating Scale), adverse events, polysomnographic parameters, subjective improvement, quality of life and clinical global impression, overall impression of the patient , the scale of Epiworth MSLT: Multiple Sleep Latency Test; PLM periodic limb movments and others. The authors evaluated the studies retrieved in searches using criteria involving the method of randomization, blinding and the method of allocation concelment. Disagreements were resolved by consensus. Results: The electronic and manual search found 1,026 studies. Were included 94 studies that met the clinical criteria for inclusion (randomized studies or quasi-randomized). The analysis of data, taken together, indicated that the pharmacological interventions were effective for dopamine agonists. Among the second-line drugs, only clonidine was shown to be effective. The quality of studies was suitable for clinical trials involving the dopamine agonists, partially adequated to levodopa and anticonvulsants, and unsuited for the other drugs studied. Conclusions: There is evidence that dopamine agonists are effective and safe for the treatment of RLS in the short term, there is no scientific evidence that all drugs are effective in this disease.